Vaccinating with a COVID-19 Vaccine: Experience of the Tertiary Allergology Center - Žilėnaitė, Eglė; Malinauskienė, Laura; Černiauskas, Kęstutis; Linauskienė, Kotryna; Kvedarienė, Violeta; Chomičienė, Anželika (Acta medica Lituanica, 2022)
Background: Allergic reactions after messenger RNA (mRNA)-based COVID-19 vaccines have been reported but detailed descriptions and further actions are not well characterized. Objective: To describe the symptoms of possible allergic reactions after the mRNA COVID-19 vaccine and outcomes of further vaccination. Methods: We descriptively analyzed data of adult (≥18 years of age) patients, who were sent for vaccination to our outpatient center for the Diagnostics and Treatment of Allergic and Immune diseases. All patients were vaccinated with the Pfizer–BioNTech Comirnaty® vaccine.Results: From January 2021 to July 2021 twenty-two patients were vaccinated in our center. Six patients experienced a reaction after the first Comirnaty® dose in different vaccination centers. The majority of them complained of various types of rashes after the first dose, one case was consistent with anaphylaxis. The latter patient was tested with the skin prick using Pfizer–BioNTech Comirnaty® vaccine and the test was negative. Other sixteen patients were vaccinated in our center from the first dose because of past allergic reactions to other medication or due to concomitant mast cell disorder. All patients were vaccinated without any immediate adverse reactions.Conclusions: None of our patients experienced repeated cutaneous reactions after the second dose. Patients with previous anaphylaxis or mastocytosis also were safely vaccinated.
Keywords: COVID-19 vaccination; allergy to vaccines; Pfizer Comirnaty